Community Knowledge on Child Gastrointestinal Disease, Growth, and Development : A Cross Sectional Study in Mandangin Islan, Sampang, Indonesia - ATHIYYAH, ALPHA FARDAH; Subijanto Marto Sudarmo; Reza Gunadi Ranuh; Andy Darma; Mira Irmawati; Khadijah Rizky Sumitro; Muhammad Irawan; Budiyanto; Novi Rahayu Arianti; Steven Christian Susianto; Sacharissa Zerlina Tsarwah Thirafi (Universitas Airlangga, 2024)
The prevalence of diarrhea in Madura is higher than in East Java. Mandangin island, an isolated island in Sampang, Madura has limited access to healthcare and knowledge. It will lead to disruptions in the children’s growth and development. This study aimed to evaluate the impact of health education on community knowledge about gastrointestinal disorders and children’s development. This cross-sectional study involved 48 subjects from Mandangin Island, Sampang by total sampling. The subjects received some presentations related to gastrointestinal disease, growth, and development in children using a handbook and audio-visual media. The subjects were required to complete pretest and posttest questionnaires. The pretest and post-test results were processed and analyzed using the statistical software “SPSS” and the Wilcoxon test. Most of the subjects were housewives with a mean age of 28.73 ± 6.22 years old. There was a significant difference between pre-and post-test in gastrointestinal disease, growth, and development in children (46.04 ± 21.71 vs 62.29 ± 13.25, p<0.001). This study found that health education through face-to-face, handbooks, and audiovisual media can enhance community knowledge.